Exploring the clinically orientated roles of the general practice receptionist: a systematic review protocol - Michael Burrows; Nicola Gale; Sheila Greenfield; Ian Litchfield (Systematic Reviews, 2017)
Abstract Background The receptionist is the focal point of the practice, undertaking an array of clinically orientated roles such as triaging patients for GP consultations or managing repeat prescribing. However, the full nature and extent of the receptionist’s clinical activities is unknown as are the implications for patients. The aim of the proposed review is to explore the nature of the receptionist’s clinical roles, their extent and their implications for patients. In doing so, we will highlight any gaps in the evidence base which future research may explore. Methods The databases Medline/PubMed, Ovid, Cinahl, ASSIA, Cochrane, EMBASE and Science Direct will be searched for relevant literature. We will look at both qualitative and quantitative research on GP receptionists, based within primary care to explore their roles within the primary care team, the clinically relevant roles they undertake, the extent of these roles and any implications these roles might have. No limits are placed on the date or place of publication; however, only research published in English will be included. Screening, quality assessments and data extraction will be carried out by two reviewers, who are not blinded to study characteristics. Analysis follows a four-stage method, established by Whittemore and Knafl (2005). Discussion The review will explore existing research covering the clinically orientated roles of the GP receptionist. The findings of the review will be important for healthcare professionals and academics working within primary healthcare. It will highlight and for the first time synthesise research relating to the complex and essential work of the GP receptionist. Our findings will inform the direction and focus of further research, as gaps in the knowledge base will be uncovered. Systematic review registration PROSPERO registration no: CRD42016048957 .